“Ineficiencia del sistema penitenciario y su connotación ante la garantía constitucional de la rehabilitación del privado de libertad” - Mullo Mayo, Walther Marcelo (2023)
The prison situation in Ecuador in recent years has experienced disastrous events in riots with criminal and bloodthirsty overtones, events that were broadcast on social networks causing social commotion. Based on this situation, the Ecuadorian prison system is questioned, concluding that this system is inefficient, the legal framework does not meet the expectations of security and respect for Human Rights. What happened in Ecuador is not an isolated event at the international level, let's remember that, in Brazil, Peru, Mexico, El Salvador; there was news of riots by inmates with the death of people. When the riots occurred in our country in the prisons of Guayaquil, Latacunga, Santo Domingo, Los Ríos, and in some of these with the death of people who were not incarcerated for major crimes, but for alimony and others with preventive detention, these crimes demand answers, for which it is concluded that there is inefficiency in the Penitentiary System, slowness of the justice system in issuing sentences, inexistence of a rehabilitation policy, crisis in the prison system; all these factors lead to confirm that there is a violation of the Constitutional Guarantee of the Rehabilitation of the Prisoner of Liberty.